Teens and the media - Hernandez,Roger E. (Philadelphia: Mason Crest Publishers, 2014)
The media have a great influence over the lives of young people, helping to determine how they dress, what they listen to, and how they think. This book will explore teens views and experiences with different media television, movies, newspapers, magazines, and the Internet and will examine how each has taken steps in recent years to attract a younger audience."--Publisher's website
Keywords: Mass media Juvenile literature